Mean streak ebook - Brown, Sandra (2014)
In this New York Times bestselling thriller, a doctor is kidnapped in the mountain wilderness after a fight with her husband — and as the FBI closes in, she must make dangerous choices to survive. Dr. Emory Charbonneau, a pediatrician and marathon runner, disappears on a mountain road in North Carolina minutes after an argument with her husband Jeff. But by the time he reports her missing, the trail has (literally) gone cold. Fog and ice encapsulate the wilderness and freeze the search. While police suspect Jeff of "instant divorce," Emory regains consciousness only to find herself the captive of a man whose violent past is so dark he won't even tell her his name. She's willing to take any risks necessary to survive. But before she can escape, the two encounter dangerous people who adhere to their own code of justice. A desperate young woman is caught at the center of a dispute, and Emory can't bring herself to look the other way, even if it means breaking the law. Rising tension and barely restrained passion blurs the lines between right and wrong, and Emory begins to wonder if the man with no name is the one who has rescued her from death . . . and from heartbreak. Combining the nail-biting suspense and potent storytelling that has made Sandra Brown one of the world's best-loved authors, Mean Streak is a wildly compelling novel about love, deceit, and the choices we must make when our lives are on the line.